DETERMINATION OF MICROSTRUCTURAL CHANGES BY SEVERELY PLASTICALLY DEFORMED COPPER-ALUMINUM ALLOY: OPTICAL STUDY - Romčević, Nebojša (Journal of Mining and Metallurgy, Section B: Metallurgy, 2014)
Our work deals with the problem of producing a complex metal-ceramic composite using the processes of internal oxidation (IO) and severe plastic deformation. For this purpose, Cu-Al alloy with 0.4wt.% of Al was used. IO of sample serves in the first step of the processing as a means for attaining a fine dispersion of nanosized oxide particles in the metal matrix. Production technology continues with repeated application of severe plastic deformation (SPD) of the resulting metal-matrix composite to produce the bulk nanoscaled structural material. SPD was carried out with equal channel angular pressing (ECAP), which allowed that the material could be subjected to an intense plastic strain through simple shear. Microstructural characteristics of one phase and multiphase material was studied on internally oxidized Cu with 0.4wt.% of Al sample composed of one phase copper-aluminum solid solution in the core and fine dispersed oxide particles in the same matrix in the mantle region. In this manner AFM, X-ray diffraction and Raman spectroscopy were used. Local structures in plastically deformed samples reflect presence of Cu, CuO, Cu2O, Cu4O3 or Al2O3 structural characteristics, depending on type of sample.